Paper-based molecularly imprinted-interpenetrating polymer network for on-spot collection and microextraction of dried blood spots for capillary electrophoresis determination of carbamazepine - Nuchtavorn, Nantana; Dvořák, Miloš; Kubáň, Pavel (Analytical and bioanalytical chemistry, 2020)
Carbamazepine is an antiepileptic drug with a narrow therapeutic index, which requires an efficient method for blood level monitoring. Finger-prick dried blood spot (DBS) collection is an alternative microsampling technique, which is less invasive than conventional venipuncture. Paper-based molecularly imprinted-interpenetrating polymer networks (MI-IPN) were developed as blood collection devices, which allowed for selective on-spot microextraction of carbamazepine from DBS. A hybrid of homogeneous polystyrene and silica gel polymer was synthesized and coated on a Whatman® Grade 1 filter paper. Proteins and other interferences in the blood samples were eliminated by using the MI-IPN collection devices, and the resulting DBS extracts were suitable for direct injection into the capillary electrophoretic instrument. The lower limit of quantitation of 4 μg/mL in capillary blood was achieved by the sweeping-micellar electrokinetic chromatography method using a KCl-containing matrix, which was sufficient for the therapeutic drug monitoring purposes. Method accuracies were in the range of 88.4 ± 4.5% to 94.5 ± 2.7% with RSD values ≤ 5.1%. The developed paper-based MI-IPN provided superior extraction efficiencies (92.2 ± 2.5%) in comparison with commercially available DBS collection cards, i.e., Whatman® 903 protein saver card (59.8 ± 2.8%) and GenCollect™ 2.0 card (47.2 ± 1.4%). The paper-based MI-IPN devices for DBS collection and on-spot extraction were characterized by simple fabrication, low costs, disposability, and reduction in sample preparation steps, and their further developments might open new perspectives in clinical applications, such as in therapeutic drug monitoring. Graphical abstract.
Keywords: Electrophoresis, Capillary; mikroextrakce na pevné fázi; Dried Blood Spot Testing; Blood Specimen Collection; elektroforéza kapilární; Anticonvulsants; Molecularly Imprinted Polymers; test suché kapky krve; monitorování léčiv; karbamazepin; Tandem Mass Spectrometry; lidé; antikonvulziva; molekulárně imprintované polymery; Paper; tandemová hmotnostní spektrometrie; odběr vzorku krve; Drug Monitoring; Solid Phase Microextraction; Carbamazepine; papír; Humans